Efektivitas Reduksi Sampah Makanan dengan Perbedaan Bioaktivator Mengunakan Metode Open Windrow di Kota Surabaya - Fauziyah Herdatul Dwi Krisdayanti; Euis Nurul Hidayah (Universitas Batanghari Jambi, 2023)
Food waste is a big problem in big cities, one of them is Surabaya. Indonesia is the second largest producer of food waste in the world. Many food scraps will be processed back into compost. This research was conducted to determine the effectiveness of using EM4 bioactivator, goat manure and deer manure in composting. The organic waste used is food waste, leftover leaves and compost starter. The composting method in this study used the open windrow method. Composting uses 6 open wind mounds with different levels of additional bioactivator. The results showed that the content of beneficial elements for plants, for levels of C/N ratio between 17.88 -19.65 in all composters. The content of the K value is between 0.39 – 0.48 and the content of the P value is between 0.40 – 0.48.